Analysis of student mathematical investigations ability on transformation geometry in terms of cognitive style - Nina Muthmainnah; Sri Subarinah; Amrullah Amrullah; Arjudin Arjudin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
Mathematical investigation is an activity that can encourage an experimental activity, collect data, make observations, identify patterns, make and test conjectures and make generalizations used to improve skills and develop students' mathematical thinking processes optimally. Different cognitive styles can affect students' ability to think and reason, especially in solving mathematical investigative problems. Therefore, this paper will examine mathematical investigations' ability in reflective and impulsive cognitive styles in qualitative descriptive analysis. The subjects in eleventh-grade senior high school at SMA Negeri 2 Mataram, Indonesia. Students were selected using a purposive sampling technique, and six students were selected as subjects in the interview consisting of three reflective students and three impulsive students. The instruments used are mathematical investigation tests, Matching Familiar Figure MFFT tests, and interview guidelines. The results showed that students with a reflective cognitive style were more thorough and systematic in writing down the answers to each point and always thought first in solving problems. Most students went through 4 stages of mathematical investigations: specialization, conjecture, generalization, and justification. While students with impulsive cognitive styles mostly managed to go through 3 stages of mathematical investigations, specialization, conjecture, and generalization, due to a lack of accuracy in solving questions and providing as simple answers as possible according to the question request.